Prioritizing Complex Issues of Hydrographic Basin Committees by Group Decision Approach - Silva, Vanessa B.S. (2010)
In Brazil, the hydrographic basin committees are the centre of decision for water resource management in their respective basins. The committee members, who represent the public sector, water users and civil society, must decide about complex issues, requesting the consideration of multiple aspects: economic, social and environmental. Given the complexity of the decision-making process, it is advantageous to have a decision support system that guarantees transparency, rapidness and, specially, a structured analysis of the problem, incorporating all aspects of the situation. This paper presents a group decision making model based on multicriteria analyses to support the members of a hydrographic basin committee to prioritize complex issues, in special activities to control the environmental degradation The proposed model works through two steps: firstly is used the PROMETHEE II method to achieve the individual rankings of alternatives, and secondly, the individual rankings of alternatives are aggregated to attain the global ranking, applying the ELECTRE IV method, reflecting the preference of the group.